Utilization and associated factors of growth monitoring and promotion services among young children in Gorkha district of Nepal - Jagat Prasad Upadhyay; Damaru Prasad Paneru; Yam Prasad Sharma; Nava Raj Khadka (BMC Nutrition)
Abstract Introduction Promotion of child health during the first thousand days from conception to the child’s second birthday is vital for survival, growth and development. Growth monitoring and promotion services are key to the early detection of growth faltering and preventing malnutrition and promoting child health. This study aimed to assess the utilization of Growth Monitoring and Promotion (GMP) services and its associated factors among young children in Gorkha district of Nepal. Methods A community-based cross-sectional study was conducted in the Gorkha district, involving 290 mother-child pairs, from April 2024 to June 2024. Multistage random sampling was used to select mothers. Data was collected through face-to-face interviews using structured questionnaires. Descriptive statistics and inferential statistics involving multivariate logistic regression analyses were performed to identify the factors associated with GMP service utilization. Results Only 5.5% of children had completed the recommended 24 GMP visits according to protocol, while 23.8% utilized GMP services more than 15 times, which represents the 75th percentile of service utilization. Mothers who had good knowledge had significantly higher (adjusted OR = 4.23, 95% CI: 2.070–8.650, p < 0.001) GMP service utilization among their children than those counterpart mothers with poor knowledge about the GMP services. The main reasons for not regular utilizing GMP services included the time constraints and their household responsibilities (85%). Conclusion This study reported the low utilization of GMP services among children in Gorkha district. Maternal knowledge on GMP service emerged as the primary predictor of GMP service utilization and maternal engagement in the household activities explores as a leading barrier to GMP service utilization. Enhancing maternal knowledge through community engagement strategies and improving the monitoring mechanism within the health systems could increase GMP utilization.